Sara Pataanguna's Dakwah Philosophy Sultan La Ode Muhammad Idrus Qaimuddin in Realizing Peace in Buton Southeast Sulawesi - Saliudin Hasim (CV. Syntax Corporation Indonesia, 2023)
In his youth , Muhammad Idrus accept Islamic education from his grandfather , the sultan of La Jampi , who had also been there became sultan with the title Sultan Qaim al-Din Tua (1763-1788). He studied under Sheikh Muhammad bin Syais Sumbul Al Makki. From this scholar He accept attraction khalwatiyah Sammaniyah . There are also many Sultan Muhammad Idrus pouring work he wrote in Arabic , Javanese script and language Wolio . Sara Pataanguna is philosophy rooted life _ from values wisdom local Butonese society and in harmony with religious values in forming character superior dignified . Pinching each other skin ( Pobinci-binciki Kuli) is manifested in four mark basic . First, Pomaa-maeka (Shame through each other ) , Second Pomaa-maasiaka ( Love each other loving ), Third Popia-piara ( mutual care ), and fourth Poangka-angkataka (mutual respect ), is expected become node unifying Buton people use it realization peace , conditionality and stability society . As for types The research used in this writing is research Qualitative approach _ studies library , namely a method of collecting data by means learn theories from various literature related to research . _ There are 4 stages in research studies References that is prepare equipment necessary tools , prepare _ bibliography work , organizing time and reading or taking notes on research material .